Comparative Outcomes and Quality Analysis of Inverted-T and Pure Vertical Scar Techniques in Superomedial Pedicle Reduction Mammaplasty. (June 2016) - Fernandez, Sarah; Coady, Loretta; Cohen-Shohet, Rachel; Molas-Pierson, Justine; Mast, Bruce A.
Abstract : Introduction: Multiple techniques exist for reduction mammoplasty, but no singular consensus exists as to which method is the most effective in providing an aesthetically pleasing breast. We reviewed our institution's reduction mammoplasty experience over a 2-year period to evaluate aesthetic and surgical outcomes comparing superiorly based pedicles with skin excisions resulting in either an inverted T or vertical scar. Methods: An IRB-approved retrospective review of our institution's surgical database identified patient characteristics and outcomes of all breast reductions performed over a 2-year period (n = 104). A subgroup analysis of patients with complete preoperative and postoperative photographs (n = 56) evaluated postoperative aesthetics on a scale of 1 to 5 (1, poor; 5, excellent). Results: Techniques included a superomedial pedicle with an inverted T-pattern skin excision (n = 81) and pure vertical reduction (n = 23). There was no significant difference in complications between techniques. Common patient risk factors (age, body mass index [BMI], and smoking status) did not correlate with postoperative complications. In the photograph analysis subgroup, inverted T scar pattern reductions had a significantly better scar quality score (3.5 vs 3.2, P < 0.05). In analysis of all subjects, volume of tissue resected was a significant factor in determining overall aesthetic score, with resections of less than 1300 g being significantly associated with an overall aesthetic score of 4 or higher. Logistic regression demonstrated patient age younger than 40 years was a significant contributor to aesthetic score of 4 or higher ( P < 0.05). Discussion: We reviewed our institution's experience with 2 common breast reduction techniques. Better scarring was associated with inverted T scar pattern versus vertical pattern. Additionally, rather than pedicle type or skin excision pattern, patient age and weight of tissue resected were the most important contributors to an aesthetically optimal outcome. This study suggests that a single superlative technique does not exist. Rather, inherent patient characteristics are most important in provision of the best aesthetic outcome.